Research of external breath parameters of gymnasts during performance of the main gymnastic exercises - Shlyakhtov, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The modern artistic gymnastics is characterized by the intensity of competitive activity and training process, and also necessity of formation of stable and reliable technique skills. The key moment in the gymnasts` preparation is improvement of functional readiness. Unfortunately, till now, it was possible to measure the data of the gas exchange and external breath only in laboratory conditions during special testing of gymnasts. In this connection the value of research of breathing system functioning during performance of the gymnastic exercises in natural conditions raises substantially. The purpose of the present research was to consider the method of ergospirometry during performance of the main gymnastic exercises as giant circles (forward and back) on the horizontal bar, swings to the handstand on the parallel bars, and acrobatic forward handspring, and to use the received data at different stages of gymnasts` training. Methods: 6 gymnasts aged 12-14 took part in the research. To study the gymnast`s external breath parameters during performance of the exercises the telemetric ergospirometry complex «Îxycon mobile» by VIASYS and specialized software package was used. The video shooting of performance of the exercises was simultaneously done and synchronized with parameters of external breath. Results: The average duration of performance of the exercises was: forward handspring 2.05 sec., forward giant circle 1.67 sec., back giant circle 1.26 sec., swings to the handstand 1.38 sec. The average parameters of the breath in (l/señ.) in this exercises were: forward handspring 2.25/1.3, forward giant circle 1.71/0.8, back giant circle 1.86/0.7, swings to the handstand 1.38/0.5. The average parameters of the breath out (l/señ.) were: forward handspring 2.18/0.7, forward giant circle 1.48/0.9, back giant circle 1.53/0.6, swings to the handstand 1.48/0.9. The short breath holding was also observed during performance of this exercises. Discussion: The received data testify that the gymnast use monotype respiratory system work that characterizes identity of its work during performance of the main gymnastic exercises as giant circles (forward and back) on the horizontal bar, swings to the handstand on the parallel bars when the breath out phase coincides with the main phase of the performance of this exercises. Performing forward handspring gymnasts use two different models of the breathing system functioning. The former - the main movements are made breathing out to strain the skeletal muscles, to reinforce the power of the performance. The latter - there is a short breath holding during the exercises to exclude extra involvement of the muscles, which leads to muscle work minimization.